Investigating the Legacies of Violence and Conflict in Transitional Justice and Peace - Onu Godwin; Kolapo Quadri Abayomi (African Journal of Political Science)
Violations of law, human rights abuse, and socio-economic and political grievances are legacies of violence and conflict-affected politics. In recent times, the aggravation of violence and conflict has hindered political development and instigated socio-economic grievances. Transitional justice and peace deal with human rights abuses, violation of rights, violence, and other grievances in societies in transition. One of the main focuses of transitional justice discourse is to engage human rights law for political stability, accountability, and peace in changes, as developed in the strict law practice. This research is descriptive and relies on secondary data. Thus, transitional justice and the rule of law are considered a framework for analysis in violence and conflict-affected politics as intertwined to promote post-violence and conflict or socio-economic and political stability. Therefore, various political actors have engaged in promoting the rule of law and the promotion of peace through security sector reform. With the focus on transitional justice, various processes have been considered through the promotion of rule of law, security, and accountability in the Niger Delta and the northeast of Nigeria that have been ravaged by insurgency, terrorism, violence, and conflict, and these processes have been supported and developed by an increasing number of actors at the national and international levels. Therefore, this paper investigates the socio-economic and political legacies of violence and conflict in transitional justice and peace and examines the interaction of transitional justice and the values of the rule of law in dealing with political tensions as shown in the cases of Boko Haram and Niger Delta. This paper recommends that transitional justice and the rule of law contribute to peace and post-conflict recovery for socio-economic and political grievances resulting from violence and conflict.